2013
DOI: 10.1091/mbc.e12-04-0282
|View full text |Cite
|
Sign up to set email alerts
|

The HSP90 inhibitor geldanamycin perturbs endosomal structure and drives recycling ErbB2 and transferrin to modified MVBs/lysosomal compartments

Abstract: The ErbB2 receptor is a validated cancer target whose internalization and trafficking remain poorly understood. The authors propose that ErbB2 internalization upon geldanamycin (GA) occurs predominantly via clathrin-mediated endocytosis and that GA affects endosomal structure and sorting, forcing recycling cargoes toward mixed endo/lysosomal compartments, irrespective of their HSP90 interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 71 publications
7
67
0
Order By: Relevance
“…8 illustrates our main concept, demonstrating that the HBV infection promotes the formation of an interconnecting reticular network between MVBs, autophagosomes and lysosomes driven by the activation of Rab7. Although tubules extending from MVBs and autophagosomes have been reported previously (Cooney et al, 2002;Cortese et al, 2013;Gao et al, 2010), those induced by HBV in the current study are much more prominent.…”
Section: Discussionsupporting
confidence: 42%
“…8 illustrates our main concept, demonstrating that the HBV infection promotes the formation of an interconnecting reticular network between MVBs, autophagosomes and lysosomes driven by the activation of Rab7. Although tubules extending from MVBs and autophagosomes have been reported previously (Cooney et al, 2002;Cortese et al, 2013;Gao et al, 2010), those induced by HBV in the current study are much more prominent.…”
Section: Discussionsupporting
confidence: 42%
“…Although HER2 internalization was found in geldanamycin‐treated cells and is a clathrin‐dependent process (Lerdrup et al ., 2007; Pedersen et al ., 2008), many studies indicated that HER2‐containing heterodimers is internalization resistant in response to ligand stimulation (Lenferink et al ., 1998; Worthylake et al ., 1999) probably due to the lack of an internalization motif in the cytoplasmic domain of HER2 (Sorkin et al ., 1993). Moreover, HER2 inhibits EGF‐induced EGFR internalization by forming EGFR/ErbB2 heterodimerization without affecting the phosphorylation or ubiquitination of EGFR (Haslekas et al ., 2005; Wang et al ., 1999), and by having a negative effect on the formation of CCP (Cortese et al ., 2013). Consistently, our data showed that EGF induced downregulation of membrane EGFR but not HER2 level.…”
Section: Discussionmentioning
confidence: 99%
“…7A). Because the number of cells with internalized aggregates is the same as in untreated cells, the reduction in the number of endolysosomes can only be explained by a role of Hsp90 in endosomal trafficking between early endosomes and lysosomes (54). Geldanamycin also affected the endosomal trafficking of PepS.…”
Section: Pepl But Not Peps Internalization Requires Hsp70 and Ismentioning
confidence: 99%